Role Model Pengembangan Kurikulum Grass Root di Sekolah Dasar - Yani Pratiwi; Sukiman Sukiman; Rohmi Triwulandari; Intan Permata Putri (Bidayatuna, 2022)
Progress in the field of education must be able to improve the quality of students. To follow these developments, it is necessary to be accompanied by the development of learning curricula by schools to improve the quality of students by adjusting the circumstances in each school. There are many models of curriculum development that can be used in schools. The research method in this article is qualitative. This field research (Field Research) aims to analyze the curriculum development model applied by SD Negeri 104 Palembang. The research finding is that the curriculum development model applied by SD Negeri 104 Palembang refers to the national education curriculum and initiates curriculum development according to school needs. The curriculum development model applied is a grass root,  the initiatives and ideas come from the principal and teachers at the school. Teachers in schools form teams to develop or perfect the curriculum, either in one or several components or its entirety.